Synthesis, Characterization And Biological Activity Of A Schiff Base Derived From Isatin And 2-Amino, 4-Methyl Phenol And Its Transition Metal Complexes - SURAJ B. ADE,; D.G. KOLHATKAR,; M.N. DESHPANDE, (International Journal of Pharma and Bio Sciences, 2012)
Biological active tridentate Schiff base ligand derived from 2-amino, 4-methyl phenol with isatin and their Ti(IV), Zr(IV), Cd(II) and Hg(II) metal complexes have been synthesized and characterized on the basis of IR, Elemental analysis, Electronic spectral data, Molar conductance and 1H NMR. The Schiff base and its metal complexes have been tested for their antimicrobial activity using disc diffusion methods and the results were interpreted.